Incidence and risk factors for amputation in Chinese patients with diabetic foot ulcers: a systematic review and meta-analysis - Zhang, Yujie; Liu, Hui; Yang, Yadi; Feng, Chaochen; Cui, Liwei (Frontiers in Endocrinology, 2024)
Objective This study aimed to comprehensively analyze the incidence of amputation in Chinese patients with diabetic foot ulcers (DFUs). Methods The Preferred Reporting Items for a Systematic Review and Meta-analysis (PRISMA) guidelines were used. The CNKI, Wanfang Data, VIP, PubMed, Web of Science, and Embase databases were searched to collect relevant literature on the incidence of amputation in Chinese patients with DFUs. Two researchers independently screened the literature, extracted data, and evaluated the risk of bias. The data were systematically analyzed using Stata 17.0 software to determine the incidence of amputation in this patient population. Results A total of 25 papers were included in the study, revealing an incidence of amputation in Chinese patients with DFUs of 22.4% (95% confidence interval: 18.3–26.5%). The subgroup analysis revealed that a history of ulcers, Wagner grade >3, and diabetic peripheral vascular disease were the primary risk factors associated with a higher incidence of amputation in Chinese patients with DFUs (P<0.05). Among Chinese patients with DFUs, the amputation group and the non-amputation group showed significant differences in body mass index, duration of DFUs, total cholesterol, triglyceride, fasting blood glucose, white blood cell count, hemoglobin A1c, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, high-sensitivity C-reactive protein, and uric acid (P<0.05). Conclusion The high incidence of amputation among Chinese patients with DFUs indicates that interventions should be implemented to prevent or minimize amputations. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42023463976.